2D Semiconductor Bi2WO6 Nanosheets as the Pt Carriers for Ethylene Glycol Oxidation Reaction with Photoelectric Interaction. Issue 7 (9th May 2019) - Gao, Haifeng; Zhai, Chunyang; Zhang, Hongmin; Fu, Nianqing; Du, Yukou; Zhu, Mingshan
Abstract : Ethylene glycol oxidation reaction (EGOR) is a key anode reaction in direct ethylene glycol fuel cells (DEGFCs). Herein, 2D semiconductor bismuth tungstate (Bi2 WO6 ) nanosheets are facilely prepared and used as carriers for the deposition of platinum nanoparticles (Pt NPs). The resultant material is used as the working electrode in the application of DEGFCs. Due to the excellent absorption property of Bi2 WO6 in visible light, the optimized Pt‐Bi2 WO6 electrode (Pt at 20 wt%) shows improved catalytic activity and stability with visible‐light illumination. The current density using the Pt‐Bi2 WO6 electrode reaches 492.5 mA mg −1 Pt with visible‐light irradiation, which is about 4.2 fold higher in comparison with the same electrode in dark conditions. This 2D sheet‐like support, together with the visible‐light response of Bi2 WO6, induces the deposition of ultra‐small sizes of Pt (5.4 nm) and the synergistic effect of electrocatalytic and photocatalytic ethylene glycol oxidation, thus greatly improving the photoelectric catalytic property of EGOR. Abstract : A synergistic effect of the electrocatalytic and photocatalytic reaction is found using 2D Bi2 WO6 as the Pt carriers for improving ethylene glycol oxidation.